Comparative Expression Analysis of Geraniol Biosynthesis genes in Differents Accessions of Cymbopogon nardus - Rofiatun Solekha; Sabilla Khoirotunnisa; Siti Lathifatul Mahmudah; Puput Virnanda Yuniar; R. Achmad Djazuli (Florea : Jurnal Biologi dan Pembelajarannya, 2026)
Citronella (Cymbopogon nardus) is rich in absorbing flavonoids, and its precious geraniol is superior, none can be compared. Despite having a number of well-known cultivars of citronella in Indonesia with unique bioactive potential, the expression profiles of genes and geraniol profile content across these plants remain unknown. Here we report on the relative expression of crucial biosynthetic and regulatory genes involved in geraniol production, analyzed in relation to β-carotene levels and geraniol content measured from five different Indonesian citronella cultivars. Gene expression was quantified using real-time quantitative PCR (RT-qPCR), targeting nine genes: CnDXS, CnIDI, CnGPPS, CnGES, CnLIS, CnUGT, CnMYB, CnGEDH, and CnGDP. Geraniol content was determined according to High Performance Liquid Chromatography (HPLC). Citrona 1 Agribun and Citrona 2 Agribun showed higher expression of the upstream biosynthetic genes (CnGES, CnGPPS) and the regulatory gene CnMYB for which showed also good linearity with highest geraniol 24.71 mg/L and 26.35 mg/L, respectively. These results demonstrate a positive expression levels and geraniol content, highlighting the transcriptional complexity in citronella geraniol biosynthesis. The conclussion, suggest possible molecular candidates for enhancing contents in biofortification scenarios (e.g., selective breeding or genome editing) for essential oil quality.